2020
DOI: 10.1111/ijlh.13225
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 contributes to drug resistance in acute myeloid leukemia by positively regulating ALG9 through sponging miR‐155

Abstract: IntroductionThe development of drug resistance is the main obstacle for successful treatment in acute myeloid leukemia (AML). Noncoding RNAs have been implicated in biological function in AML drug resistance. Aberrant protein glycosylation is associated with AML progression. The aim of the study was to explore the potential regulatory mechanism of lncRNA MEG3/miR‐155/ALG9 axis in drug resistance of AML.MethodsQRT‐PCR and Western blot were used for comparison analyses of ALG9, MEG3, and miR‐155 levels. CCK‐8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…A study show that LncRNA MEG3 regulates ALG9 by sponging miR-155 (26) and miR-155 regulates the pathogenesis of heart failure (27). These results are consistent with our experimental results.…”
Section: Discussionsupporting
confidence: 91%
“…A study show that LncRNA MEG3 regulates ALG9 by sponging miR-155 (26) and miR-155 regulates the pathogenesis of heart failure (27). These results are consistent with our experimental results.…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, although current literature shows no evidence for “MEG3” functions in GD, DES-Tcell suggests a potential association of this lncRNA to GD. This idea is strengthened by the Yu et al study that shows ‘miR-155’ (that we know to be involved in GD) is a direct target of the ‘MEG3’ which acts by sponging ‘miR-155’ in acute myeloid leukemia (AML) cells 113 . Therefore, this DES-Tcell association is suggested as potentially new immunological knowledge and should be considered a potential therapeutic target.…”
Section: Knowledgebase Utilities and Case Studiesmentioning
confidence: 99%
“…Some literatures have shown that ceRNA network participates in the occurrence of MDR in cancers, including nasopharyngeal carcinoma ( Wang et al, 2020 ) and AML ( Yu et al, 2020 ). However, except for one paper ( Zhang et al, 2019 ), there is no other report on ceRNA regulatory network and its role in MDR-CML.…”
Section: Discussionmentioning
confidence: 99%